The death of conservative Ireland? The 2018 abortion referendum. (June 2020) - Elkink, Johan A.; Farrell, David M.; Marien, Sofie; Reidy, Theresa; Suiter, Jane
Abstract: The outcomes of two recent Irish referendums - on marriage equality in 2015 and abortion in 2018 - have placed contemporary Irish voters in sharp contrast with their long-standing conservative Catholic reputation. These referendums also stand out internationally because of an associated deliberative innovation. This paper aims to explain the watershed abortion vote drawing on theories of generational change, issue-voting, cue-taking and deliberative democracy, using data from an exit poll at the 2018 abortion referendum. We show that cleavage and age effects are key to understanding the referendum outcome. These results offer insight into how societal processes such as rapid secularisation, generational replacement and democratic innovations shape politics. Moreover, voters who were aware of the deliberative innovation were more likely to support the liberal referendum option. To increase willingness to deviate from the status quo, engaging citizens actively in the debate is a fruitful approach.